Main outcomes of stroke rehabilitation: A multi-centre study in Thailand - Vilai Kuptniratsaikul (2018)
Objective: To estimate the efficiency of inpatient rehabilitation for patients after stroke in Thailand. Design: Multi-centre, prospective study. Subjects: Patients after stroke, aged ≥18 years, with stable medical signs, able to follow 1-step commands and to sit for at least 30 min. Methods: Main outcomes included Barthel Index (BI) scores, BI effectiveness, BI efficiency, length of stay, Thai Hospital Anxiety and Depression Scale (HADS) scores, and quality of life. Results: Of a total of 327 patients, 285 completed the programmes, with a mean length of stay of 27.3 days. Mean age was 62.1 (standard deviation (SD) 12.1) years and 59% of patients were male. Mean BI scores on admission and at discharge were 7.48 (SD 3.96; range 0-19) and 13.27 (SD 4.86; range 0-20), respectively. The change score was 5.79 (SD 3.89) and the efficiency of functional score was 0.28 points/ day. Using multivariate analysis, factors associated with change in BI score were age, previous stroke and length of stay. Sixty-four patients (25.5%) had anxiety and 95 (37.8%) had depression on admission. At discharge, the numbers of patients with anxiety and depression decreased to 17 (6.8%) and 41 (16.3%), respectively. The quality of life scores at discharge were significantly higher than those on admission. Conclusion: Inpatient rehabilitation enabled stroke patients to reach optimal functional ability, and improved psychological status and quality of life. © 2009 The Authors. Journal Compilation © 2009 Foundation of Rehabilitation Information.